Pengaruh Konflik Pekerjaan-Keluarga dan Konflik Keluarga- Pekerjaan Pada Niat Karyawan Untuk Keluar dari Pekerjaannya Dengan Gender, Dukungan Sosial, dan Nilai Individu Keluarga Sebagai Variabel Pemoderasi - , PUTU IRMA YUNITA, Dr. Gugup Kismono, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this research to examine the conflict between work and family (work interfere family-WIF and family interfere work-FIW) and its influence to turnover intention. This research also examine the moderating effect of gender, social support and individual value to see how these variables affect the relationship between work family conflict and turnover intentions. This study use 210 low and middle manager of four and five star hotels in Bali as a respondents. That sample consists of 126 male and 84 female. Multiple regression analyses and hierarchical analyses were used as a statistical method to test the proposed hypotheses. The result shows that WIF has a positive influence and significantly related to turnover intention whereas FIW has no influence on turnover intention. It is also found that social support significantly moderates the relationship between work family conflict (WIF and FIW) and turnover intention. Whereas, gender and individual value have no impact on relationship between work family conflict (WIF and FIW).